2019
DOI: 10.1515/jpem-2019-0214
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of GnRH agonist treatment on body mass index in girls with idiopathic central precocious puberty

Abstract: IntroductionStudies evaluating effects of gonadotropin-releasing hormone agonist (GnRHa) on weight and body-mass-index (BMI) in girls with idiopathic central precocious puberty (iCPP) include short-term effects. The aim of this study is to investigate changes in BMI during and 2 years after completion of GnRHa to determine the factors that may impact BMI in girls with iCPP.MethodsMedical files of 138 girls who completed GnRHa were evaluated. All patients had weight and height measurements at the beginning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…All patients underwent clinical and hormonal assessments every six months until treatment completion. At 3 months of treatment, a GnRH stimulation test was performed to define peak LH levels below 2 IU/L to indicate suppression of the hypothalamic-pituitary-gonadal axis [ 33 ]. The patients visited the hospital within 3 months of menarche.…”
Section: Methodsmentioning
confidence: 99%
“…All patients underwent clinical and hormonal assessments every six months until treatment completion. At 3 months of treatment, a GnRH stimulation test was performed to define peak LH levels below 2 IU/L to indicate suppression of the hypothalamic-pituitary-gonadal axis [ 33 ]. The patients visited the hospital within 3 months of menarche.…”
Section: Methodsmentioning
confidence: 99%
“…There has been controversy about the association between GnRHa treatment and weight gain or obesity [ 24 ]. Several studies have shown increased BMI SDS during GnRHa treatment and decreased BMI SDS after discontinuation of GnRHa [ 25 - 28 ]. In a study with a 1-month GnRHa depot formulation, the proportion of normal weight, overweight, and obese subjects did not differ significantly before and after discontinuation of GnRHa treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…24) Several studies showed increased BMI SDS during GnRHa treatment and decreased BMI SDS after discontinuation of GnRHa. [25][26][27][28] In a study with 1-…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…The incidence of sexual development disorders in children, especially precocious puberty, has increased significantly in recent years and has become one of the most common pediatric endocrine diseases [9,10], and idiopathic central precocious (idiopathic central precocious puberty, ICPP) is especially important. The direct cause of ICPP is early initiation of the GnRH secretion pulse in the hypothalamus and the increase of the overall level, which activates the pituitary and downstream gonadal organs such as the ovaries and uterus, and makes the HPG axis reach the puberty state prematurely [11,12]. However, the mechanism underlying the abnormal increase in GnRH secretion requires elucidation and is the subject of current research.…”
Section: Discussionmentioning
confidence: 99%